EFFECTS OF HONEY ON SURVIVAL AND GROWTH PERFORMANCE OF Clarias gariepinus (BURCHELL, 1822) FINGERLINGS - BAMAIYI, C; BALOGUN, J. K.; AUTA, J.; NASIRU, S. S.; UMAR, B. D. (Nigerian Journal of Fisheries, 2019)
Effects of honey on survival and growth performance of C. gariepinus (Burchell, 1822) fingerlings were investigated. The experiment constituted of T1 (0ml/g): Control; T2 0.1ml of honey/g of feed); T3 0.2ml of honey/g of feed; T4 0.3ml of honey/g of feed; T5 0.4ml of honey/g of feed and three replicates using complete randomized design (CRD). Data collected analyzed using one-way analysis of variance to test for significant difference (P<0.05) on survival and growth performance, means separation was done by Duncan's Multiple Range Test. The results showed that treatment T2 (0.1ml/g) had the highest mean survival rate (95.33 %) and was significantly different (P<0.05) compared to control (T1). Similarly, T2 (0.1ml/g) was significantly different (P<0.05) from T4 (0.3ml/g) and T5 (0.4ml/g) at (P<0.05). Survival rate of fingerlings decreased with increased honey concentrations. Growth parameters such as weight gain (2.26g), percentage weight gain (80.74%), specific growth rate (1.01%), SLI (6.38cm) showed that treatment T2 (0.1ml/g) had the highest growth performance and was significantly higher than that of control (T1) (0ml/g) at (P<0.05). This study showed that honey in fish diets improved survival and growth performance of C. gariepinus fingerlings. Therefore, recommended that honey can be incorporated in fish diets in aquaculture. Keywords: , , F, , , and